Efficacy of acupuncture in patients with carotid atherosclerosis: a randomized controlled clinical trial - Xichang Huang; Lingcui Meng; Lin Zhao; Shuang Yang; Danhui Lai; Jianxing Zhang; Xiaoxi Wu; Yanhui Jiang; Junhe Zhou; Peng Zhou; Wenbin Fu (BMC, 2024)
Abstract Background The current clinical management of carotid atherosclerosis is based on the control of risk factors and medicine. However, the risk of adverse events associated with the medicine resulting in concerns and low medication compliance makes it necessary to seek a safer alternative therapy. This study assessed the effectiveness and safety of acupuncture as a treatment for carotid atherosclerosis. Methods In this randomized controlled trial, patients with carotid atherosclerotic plaques were included and randomly assigned (1:1) to receive real acupuncture or sham acupuncture for 12 weeks. The follow-up period was 12 weeks. The primary outcome included carotid intima-media thickness (cIMT), plaque score (PS), plaque volume (PV) and grey-scale median (GSM). Secondary outcome was pulse wave velocity (PWV). Adverse events results were recorded as safety outcomes. Results From January 2021 to February 2022, 60 eligible patients were included. 55 patients (91.7%) completed the intervention and the 12-week follow-up and there was no statistical difference in demographics between the groups. At the end of treatment, the real acupuncture group had significantly reduced PS (P = 0.002), PV (P = 0.000), and improved GSM (P = 0.044). There was no significant difference in the reduction in cIMT (Left cIMT: P = 0.338, Right cIMT: P = 0.204) and PWV between the groups (the left BS: P = 0.429; the left ES: P = 0.701; the right BS: P = 0.211; the right ES: P = 0.083). Three mild adverse reactions occurred during the study. Conclusion This study found that acupuncture had a certain effect on reducing the thickness and volume of carotid plaque and improving the stability of plaque with minor side effects. These findings suggest that acupuncture may be a potential alternative therapy for carotid atherosclerosis. Trial registration This trial has been registered at ClinicalTrials.gov (ChiCTR2100041762). Submitted 30 December 2020, Registered 4 January 2021 Prospectively registered.